2020
DOI: 10.3390/cancers12040866
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Radiogenomics Approach for Risk Assessment of Post-Operative Metastasis in Pathological T1 Renal Cell Carcinoma: A Pilot Retrospective Cohort Study

Abstract: Despite the increasing incidence of pathological stage T1 renal cell carcinoma (pT1 RCC), postoperative distant metastases develop in many surgically treated patients, causing death in certain cases. Therefore, this study aimed to create a radiomics model using imaging features from multiphase computed tomography (CT) to more accurately predict the postoperative metastasis of pT1 RCC and further investigate the possible link between radiomics parameters and gene expression profiles generated by whole transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…Payel Ghosh et al provided a radiomic-genetics pipeline that can extract 3D intra-tumor heterogeneity features from CECT images and explore associations between features and gene mutation status (36). A proposed integrative radiogenomics method could evaluate risk of postoperative metastasis in KIRC with pathological stage T1, which would be beneficial for postsurgical metastasis treatment of KIRC patients (37). Burak Kocak et al provided a radiomic model to predict histopathologic nuclear grade by using the radiomic features extracted from unenhanced CT texture analysis of KIRC tumors (13).…”
Section: Discussionmentioning
confidence: 99%
“…Payel Ghosh et al provided a radiomic-genetics pipeline that can extract 3D intra-tumor heterogeneity features from CECT images and explore associations between features and gene mutation status (36). A proposed integrative radiogenomics method could evaluate risk of postoperative metastasis in KIRC with pathological stage T1, which would be beneficial for postsurgical metastasis treatment of KIRC patients (37). Burak Kocak et al provided a radiomic model to predict histopathologic nuclear grade by using the radiomic features extracted from unenhanced CT texture analysis of KIRC tumors (13).…”
Section: Discussionmentioning
confidence: 99%
“…A set of recommendations was established for the reporting of the studies assessing prediction models to minimize bias and to increase their clinical usefulness [ 18 ]. A relatively large number of radiomics studies are pilot or feasibility studies, but they do not provide open data or the codes [ 17 , 19 , 20 ]. This prevents validation analyses to confirm the respective results.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have made efforts to explore the association of radiomic features and transcriptomic data (18,38). Lee et al (16) found that a four-feature radiomic signature could predict the clinical outcomes of pathological T1 renal cell carcinoma and was associated with the abundance of certain immune cell types. This was consistent with our ndings, but the exact mechanisms of forming an immunosuppressive microenvironment in tumors with low peritumoral heterogeneity were not explored in this article.…”
Section: Discussionmentioning
confidence: 99%
“…First, radiomics is a non-invasive method to infer tumor characteristics and can be carried out several times during treatment (11,14,15). Moreover, compared to genomic sequencing, which selects only a small part of the tumors, radiomics elucidates the landscape of a tumor and is not subjected to selection bias, and thus could comprehensively explore tumor heterogeneity (16)(17)(18). Previous studies focused on radiomic texture analysis have quanti ed tumor heterogeneity and suggested its associations with unfavorable prognosis in breast cancer (19,20).…”
Section: Introductionmentioning
confidence: 99%